Designing and implementing an integrated non-communicable disease primary care intervention in rural Nepal. Issue 2 (29th April 2019) - Kumar, Anirudh; Schwarz, Dan; Acharya, Bibhav; Agrawal, Pawan; Aryal, Anu; Choudhury, Nandini; Citrin, David; Dangal, Binod; Deukmedjian, Grace; Dhimal, Meghnath; Dhungana, Santosh; Gauchan, Bikash; et al.
Abstract : Low-income and middle-income countries are struggling with a growing epidemic of non-communicable diseases. To achieve the Sustainable Development Goals, their healthcare systems need to be strengthened and redesigned. The Starfield 4Cs of primary care—first-contact access, care coordination, comprehensiveness and continuity—offer practical, high-quality design options for non-communicable disease care in low-income and middle-income countries. We describe an integrated non-communicable disease intervention in rural Nepal using the 4C principles. We present 18 months of retrospective assessment of implementation for patients with type II diabetes, hypertension and chronic obstructive pulmonary disease. We assessed feasibility using facility and community follow-up as proxy measures, and assessed effectiveness using singular 'at-goal' metrics for each condition. The median follow-up for diabetes, hypertension and chronic obstructive pulmonary disease was 6, 6 and 7 facility visits, and 10, 10 and 11 community visits, respectively (0.9 monthly patient touch-points). Loss-to-follow-up rates were 16%, 19% and 22%, respectively. The median time between visits was approximately 2 months for facility visits and 1 month for community visits. 'At-goal' status for patients with chronic obstructive pulmonary disease improved from baseline to endline (p=0.01), but not for diabetes or hypertension. This is the first integrated non-communicable disease intervention, based on the 4C principles, in Nepal. Our experience demonstrates high rates of facility and community follow-up, with comparatively low lost-to-follow-up rates. The mixed effectiveness results suggest that while this intervention may be valuable, it may not be sufficient to impact outcomes. To achieve the Sustainable Development Goals, further implementation research is urgently needed to determine how to optimise non-communicable disease interventions.